The role of foreign direct investment and trade on carbon emissions in Turkey - Gizem Kaya; M. Özgür Kayalica; Merve Kumaş; Burc Ulengin (Environmental Economics, 2017)
This study aims to observe the long run and short run effects of gross domestic product, foreign direct investment inflows and trade on CO2 emissions and causality relationships between these factors, using annual data for the period of 1974-2010. The empirical results demonstrate that the inverted U-shaped relationship of environmental Kuznets curve is valid for Turkey. In addition, there are positive long run effects of foreign direct investment and trade openness on CO2 emissions. The authors also find a bidirectional causality relationship between CO2 emission and FDI.